An Evaluation Using Cloud Services for Car-To-Car Communication - Yogarayan, Sumendra; Azman, Afizan; V Devarajan, Logaraj; Chandran, Premnath; Fatimah Abdul Razak, Siti; Jai Raman, Kirbana; Fikri Azli Abdullah, Mohd; Zainab Ibrahim, Siti; Sonai Muthu, Kalaiarasi (International Journal of Engineering and Technology, 2018)
Modern hand-held devices such as smartphones and tablets have become high in demand. Wide range of commercial concepts and possibilities have come into the limelight due to the extra features fitted in these devices. In particular, most smartphones and tablets regularly include cameras, high-speed processors, GPS and internet access. With emerging technology, there are many applications that allow the processing of real time information and location based services. Mobile devices from various platforms gain much popularity and become more advanced these days. In short, we are using them to accomplish our daily tasks. Hence, two applications are developed and tested with cloud services integration.
Keywords: car communication; cloud services; platform; android; GPS